New Treehouses of the World - Nelson, Peter (New York Abrams, 2009)
Since the publication of Treehouses of the World, the community of treehouse builders has grown tremendously, and many more innovative treehouses have been built around the world. In New Treehouses of the World, world-renowned treehouse designer and builder Pete Nelson takes readers on an exciting, international tour of more than 35 new treehouses that reveal how treehouses are designed, constructed, and appreciated in a wide array of cultures and settings.
Include Color Illustrations, Resources and Index.
New Tree Houses of the World.
Keywords: Tree houses